Early Experimental Results of Nerve Gap Bridging with Silicon Microwires - Likhodiievskyi, Volodymyr (Innovative Biosystems and Bioengineering, 2019)
Background. The incidence of severe peripheral nerves and plexus injuries tends to grow. Autoneurografting is considered as a golden standard method of nerve gap bridging, but existing shortcomings such as additional surgery measures, denervation of other segments of the body, discordance of the neurovascular structure of the damaged nerve and autograft stipulate the development of new material and treatment methods. Objective. The current study is aimed at estimation of the impact of silicon wires on early morphological changes of the parts of the damaged peripheral nerve after nerve injury and grafting with the use of silicon wires. Methods. Study was performed on Wistar rats that were divided into groups: I (n = 10) was sham-operated, II (n = 10) with 10 mm sciatic nerve gap bridged with autoneurograft, III (n = 10) with nerve gap bridged with freeze-thaw decellularized allogenic aorta filled with 4% carboxymethylcellulose hydrogel, IV (n = 10) with nerve gap bridged with same conduit as III along with longitudinal oriented silicon wires (p-type, Boron-ligated). Parts of the sciatic nerve were harvested for histologic study: 1 week postoperatively the proximal nerve stump, proximal stump-to-graft site and graft site itself were analyzed. 3 weeks after surgery the proximal nerve-to-graft junction and graft site were analyzed. Longitudinal frozen sections were stained with nitric silver via modified Bielschowsky method. The number of nerve fibers was statistically measured and compared. Results. It is stated that 1 week after surgery rats from groups II, III, and IV demonstrated signs of nerve fibers irritation in proximal nerve stump. Proximal nerve-to-graft junction contained thin nerve fibers and moderate amount of cells in group II, but a substantial amount of cells, blood vessels and newly-formed nerve fibers in groups III and IV. Graft site contained degenerated nerve fibers in group II, homogeneous semi-transparent masses in group III and same masses with silicon wires in group IV. 3 weeks after surgery rats from group II demonstrated heterogeneous chaotic distribution of nerve fibers at the proximal nerve-to-junction site and heterogeneous distribution of nerve fibers at the graft site. Group III had proximal neuroma site that was composed of substantial amount of chaotically oriented nerve fibers. Graft site contained thin heterogeneously distributed nerve fibers inside the conduit, which were situated alongside the conduit wall or close to vessels. Group IV had proximal neuroma site that was composed of newly-formed nerve fibers that were situated in certain order and mixed with cells and vessels. At the conduit site, thin nerve fibers grow inside conduit lumen, mixed with vessels, and shift towards the silicon wires. Conclusions. It can be concluded about the possible tendency of the pro-regenerative effect of silicon wires, used as a component of the nerve graft, as evidenced by more homogeneous and complete graft site neurotization along with the possible appearance of the nerve interface "nerve fiber–silicone microwire".